Analysis of Reading and Writing Al Quran Difficulties in Islamic Religious Education learning at Class IX SMP Negeri 1 Colomadu - Nur Aisyah, Aqiila Khairunisa; Salim, Hakimuddin (ISTAWA, 2024)
ABSTRACT: Learning and teaching the Koran is obligatory because the Koran is a guide to life for Muslims. However, learning it is certainly not easy and experiences various difficulties. This research aims to analyze students' difficulties in reading and writing the Al - Qur’an  الْكَرِيمُwhen learning Islamic Religious Education (PAI) at SMP Negeri 1 Colomadu. This research used a descriptive qualitative method with the research subjects being class IX students and PAI teachers. The results of the research show that the difficulties faced by students include the inability to recognize hijaiyah letters, connect the letters, and read according to tajweed rules. This research also highlights the factors that cause these difficulties, which include internal factors such as low motivation and lack of interest in students, as well as external factors such as family factors, less varied learning media, limited time, and teacher qualifications. Efforts to overcome students' difficulties are carried out by implementing more varied learning methods, personality approaches and special guidance, increasing practice hours, involving parents and the home environment, and carrying out periodic evaluations.